Evaluation of two Humphrey perimetry programs: Full threshold and SITA standard testing strategy for learning effect - ŞAHİN, ÖZLEM (WICHTIG EDITORE, 2005)
PURPOSE. To compare learning effect of Swedish interactive threshold algorithm (SITA) standard strategy with full threshold testing. METHODS. Thirty-nine medical students with no experience in visual field testing had full threshold (FT) and SITA standard for either right or left eyes. They were chosen in such a way that 20 (Group I) had FT for right and SITA for left eyes and 19 (Group II) had SITA standard for right and FT for left eyes. It was designed to have both strategies on same person whereby eliminating inter-individual variability. Visual field testing was repeated in the same week of the first test on the same subject with the same strategy that was chosen for that eye. RESULTS. The authors found an improvement in mean deviation (MD) and pattern standard deviation (PSD) of first and second testings correspondingly for FT (MD from -3.04 to -2.55; PSD from -2.60 to -2.29) and SITA standard (MD from -2.86 to -2.20; PSD from 2.25 to 2.10) and changes were statistically significant (p < 0.05). To analyze learning effect of visual field testings, we calculated percentage change in MD and PSD for full threshold and SITA standard strategy. The percentage changes in visual field parameters were significantly lower in SITA standard strategy testing for MD (p=0.02) and PSD (p=0.01). CONCLUSIONS. This study shows that a learning effect is present for both strategies and SITA standard may have a reduced learning effect compared to FT.
Keywords: learning effect; full threshold; SITA; VISUAL-FIELD DEFECTS; AUTOMATED PERIMETRY; PATIENT EXPERIENCE; GLAUCOMA; ALGORITHM; SENSITIVITY; FASTPAC